35 'Plugging the gaps': healthcare professionals' responses to challenges in providing palliative care out-of-hours in the community. (30th January 2023) - Goodrich, Joanna; Gaczkowska, Inez; Firth, Alice; Harding, Richard; Murtagh, Fliss; Evans, Catherine
Abstract : Introduction: Services providing palliative care out-of-hours vary considerably across the UK, and resources are generally limited, which presents considerable practical and emotional challenges for the specialist and non-specialist healthcare staff involved in providing care. The ways in which healthcare professionals respond may vary, and may come at some personal cost. Aims: To identify the ways in which healthcare professionals respond to the challenges in providing palliative care out-of-hours to patients in the community. Methods: Semi-structured qualitative interviews with purposively sampled healthcare professionals involved in provision of out-of-hours community palliative care in the UK. Verbatim transcripts were analysed using reflexive thematic analysis. Results: 28 interviews were conducted with 39 participants, including: GPs, community nursing teams, and palliative care medical consultants and specialist nurses providing care across 20 areas in the UK. Themes related to responding to the challenges in the provision of care out-of-hours were: planning and anticipating patients' needs out-of-hours; innovative ways of working; challenge of working within limited resources; moral distress among healthcare professionals. The themes were mapped onto four overarching models of out-of-hours care, which represent varied and inequitable provision (with some having more 'gaps' than others) across the UK. Improved planning and innovations in some services, such as increasing access to medicines through nurse prescribers, and providing palliative care training to paramedics out-of-hours have been positive responses but these are not universal across all models of care. Conclusions: Healthcare professionals are faced with many challenges in providing good quality out-of-hours care to patients in the community, including an overstretched workforce. Responses across services vary, leading to innovations, but also staff distress. Impact: This study highlights how staff work to 'plug gaps' in out-of-hours palliative care to manage patients' care within limited service provision and marked inequity across the UK. It should inform better strategic planning and provision by commissioners and service providers.